Genome-Wide Association Analysis Reveals the Genetic Basis of Iron-Deficiency Stress Tolerance in Maize - Xu, Jianqin; Xu, Weiya; Chen, Xulei; Zhu, Huaqing; Fu, Xiuyi; Yu, Futong (Frontiers in Plant Science, 2022)
Iron (Fe) is an essential trace element for almost all organisms and is often the major limiting nutrient for normal growth. Fe deficiency is a worldwide agricultural problem, which affects crop productivity and product quality. Understanding the Fe deficiency response in plants is necessary for improving both plant health and the human diet. In this study, Fe-efficient (Ye478) and Fe-inefficient maize inbred lines (Wu312) were used to identify the genotypic difference in response to low Fe stress during different developmental stages, and to further determine the optimal Fe-deficient Fe(II) supply level which leads to the largest phenotypic difference between Ye478 and Wu312. Then genome-wide association analysis was performed to further identify candidate genes associated with molecular mechanism under different Fe nutritional status. Three candidate genes involved in Fe homeostasis of strategy II plants (strategy II genes) were identified, including ZmDMAS1, ZmNAAT1 and ZmYSL11. Furthermore, candidate genes ZmNAAT1, ZmDMAS1 and ZmYSL11 were induced in Fe-deficient roots and shoots, expression of ZmNAAT1 and ZmDMAS1 responded to Fe deficiency more in shoots than in roots. Beyond that, several genes that may participate in Fe homeostasis of strategy I plants (strategy I genes) were identified, which were either encoding Fe transporters (ZmIRT1, ZmZIP4), or acting as essential ethylene signal transducers (ZmEBF1). Interestingly, ZmIRT1, ZmZIP4 and ZmEBF1 were significantly up-regulated under low Fe stress, suggesting that these genes may be involved in Fe deficiency tolerance in maize which is considered as strategy II plant. This study demonstrates the use of natural variation in the association population to identify important genes associated with Fe deficiency tolerance, and may further provide insights for understanding the molecular mechanism underlying the tolerance to Fe-deficiency stress in maize.